2021
DOI: 10.1037/rep0000388
|View full text |Cite
|
Sign up to set email alerts
|

The role of specific sources of social support on postinjury psychological symptoms.

Abstract: Purpose/Objective: The role of perceived social support from specific sources (e.g., families, friends, and significant others) on the development of postinjury posttraumatic stress disorder (PTSD) and associated psychological symptoms (e.g., depression and anxiety) remains relatively unexplored. We examined the predictive role of social support from specific sources on psychological symptoms among emergency department (ED) patients following motor vehicle crash (MVC). Research Methods/Design: Sixty-three inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…Social support has been considered in research as an important outcome in determining recovery of trauma patients (73)(74)(75). It can be in the form of physical care, financial aid, or emotional relief (76)(77)(78). The role of caregivers, especially in settings with limited affordable and available rehabilitative services, has been recognized as being particularly vital.…”
Section: Discussionmentioning
confidence: 99%
“…Social support has been considered in research as an important outcome in determining recovery of trauma patients (73)(74)(75). It can be in the form of physical care, financial aid, or emotional relief (76)(77)(78). The role of caregivers, especially in settings with limited affordable and available rehabilitative services, has been recognized as being particularly vital.…”
Section: Discussionmentioning
confidence: 99%
“…Social support significantly mediated the relationship between psychological well-being and health-risk behaviors (Lai & Ma, 2016). Similar to Lai and Ma (2016), Brienza et al (2021) found that the strength of perceived social support impacted the severity of depressive symptoms and post-traumatic stress disorder symptoms experienced. Brienza et al (2021) assessed 63 individuals (37 women, 26 men; Mage = 37 years) who experienced a sudden disruption (i.e., motor vehicle crash) to examine the role of social support on psychological symptoms.…”
mentioning
confidence: 70%
“…Individuals experiencing higher depressive symptoms and post-traumatic disorder symptoms were predicted by lower perceived social support (Brienza et al, 2021).…”
mentioning
confidence: 95%